Exploring Ultrasonographic Atypical Aspects in Drug‐Resistant Multifocal Chronic Inflammatory Demyelinating Polyneuropathy - Angela Puma; Aurora Parrotta; Nicolas Azulay; Andra Ezaru; Michele Cavalli; Mihai Ioncea; Luisa Villa; Nicolae Grecu; Giulia Tammam; Sabrina Sacconi; Simona Maccora; Charles Raffaelli (Brain and Behavior)
ABSTRACT Introduction/aims Chronic inflammatory demyelinating polyneuropathy (CIDP) and its variants are characterized by nerve enlargement (NE), particularly in the proximal segments of the median nerve (MN) and cervical roots, as assessed by ultrasound (US). NE is typically moderate and seldom exceeds double the normal size of the cross‐sectional area (CSA). Furthermore, limited knowledge exists regarding the changes in the internal structure of nerves evaluated with high‐frequency ultrasound. This study describes three cases of significant CIDP‐NE assessed with an ultra‐high‐frequency probe (UHF‐US; 33 MHz) showing how changes in US‐nerve images may guide treatment choice. Methods Three patients diagnosed with multifocal CIDP and followed for several years in our department were studied. Clinical evaluations, electrodiagnostic studies (EDX), laboratory analyses, and UHF‐US of the nerves were performed. Results Nerve conduction studies (NCS) revealed severe demyelinating neuropathy with conduction blocks, reduced motor conduction velocities (MCV) in all cases, and secondary axonal degeneration in two cases. Ultrasound showed NE in the roots and nerves, with altered echogenicity and modification of internal nerve structure. A second‐line treatment was successfully started in three patients. Discussion UHF‐US allows for the evaluation of structural changes in the nerve. NE and alterations in internal structure can be considered ultrasound markers of disease severity, guiding therapeutic decisions.